Abstract 11457: Long Noncoding RNA LncAPAT Promotes Atherosclerotic Plaque Instability by Targeting Ribosomal Protein L22 - Kamili, Adalaiti; Li, Rongxia; Yang, Shujun; Zhang, Weili (Circulation (New York, N.Y.), 2022)
IntroductionAtherosclerosis is a chronic inflammatory disorder and macrophages play a critical role in the progression of atherosclerosis. Long noncoding RNAs (lncRNAs) participate in the process of macrophage inflammation and atherosclerosis. But the molecular mechanisms underlying the function of lncRNAs in macrophages during the development of atherosclerosis are largely unknown. HypothesisWe hypothesized that lncRNAs may regulate inflammatory response of macrophages and atherosclerotic plaque instability. Methods and ResultsSubjects with suspected coronary artery disease were examined by coronary computed tomography angiography and divided into control (without >1 mm2 lesions) and mixed plaque groups (with plaques containing lipid, fibrous and calcified components). With whole transcriptome sequencing and further confirmation of real-time PCR in peripheral bloods, a novel lncRNA (named hereafter, atherosclerotic plaque instability associated transcript, lncAPAT), was identified to express at high levels in patients with mixed plaques. A murine model with monocyte-specific knock in of lncAPAT was generated. (LncAPAT significantly promoted plaque burden by 1.67-fold in the aorta of MØlncAPAT mice compared with control group (MØcontrol mice). Immunofluorescence analysis showed an elevated numbers of macrophage (by 88%) and increased expression of matrix metalloproteinase (MMP) (MMP9 by 7.7-fold and MMP2 by 86%) in plaques of MØlncAPAT mice. LncAPAT significantly promoted monocytes adhesion to endothelium in vitro and increased the expression of tumor necrosis factor α and intercellular adhesion molecule 1. LncAPAT also enhanced the lipid uptake ability of macrophages. Chromatin isolation by RNA purification-sequencing assay showed that lncAPAT interacted directly with the promoter region of the ribosomal protein L22 gene (RPL22), and it promoted inflammatory response of macrophages by inhibiting the transcriptional activity of RPL22. Conclusion(s)Our findings first identified that lncAPAT was upregulated in patients with coronary vulnerable plaques and promoted the inflammatory response of macrophages by inhibiting the transcriptional activity of RPL22, thereby contributing to plaque instability.